Water rights and water rights trading: Option for the Yellow river basin? - Cenacchi, Nicola; Xue, Yunpeng; Xinfeng, Fu; Ringler, Claudia (International Food Policy Research Institute, 2010)
Clearly defined and legally enforceable water rights and responsibilities for water operators and users in an irrigation system are the foundation underlying the incentives for conserving water and improving irrigation efficiency.